Application of problem-solving learning models to improve the activity and students' learning outcomes of SMA Kristen YABT Manokwari - Samara, Nengsi; Yohanita, Aksamina M; Iwan, Iwan (Inornatus: Biology Education Journal, 2018)
The study aims to improve students activity and achievement cognitive in glade XI IPA Kristen YABT Manokwari school year 2017/2018 on the material of Human Circulation System by applying Problem Solving Learning. Classroom action research is conducted in two cycles, each cycle consists of four stage s of planning, implementation, observation, and reflection involving students as much as 13 people. Data collection is done through observation sheets and test provision. The result of this research shows that the students activity cycle average is 64,9% and on the second cycle the average of student activity reach 77,8% and most of student have reached active criteria. On the result of student learning in cycle I that is 59,61 not yet completed by minimum masteri criteria but has reached the completeness i n classical that is 76,92%. The average grade obtained by students in the second cycle 74.61% and students' classical learning completeness on the second cycle increased to reach 92.3%. Based on the results of research that has been done can be concluded that the application of problem solving learning can improve the activity and achievement of students in the learning process.